Maqasid al-Syariah in the Federal Constitution: A Preliminary Exposition: (Maqasid al-Syariah dalam Perlembagaan Persekutuan: Suatu Perbahasan Awal) (Kanun: Jurnal Undang-undang Malaysia, 2016)
Maqasid al-syariah (high intent of law) refers to the universal principles of benefit to mankind that are obtained via Islamic texts or authority. Meanwhile, the Federal Constitution is the supreme law of the country which contains peculiar elements that are certain ideology and peculiar elements. A discussion of both of these together is a new discourse, attempting to uncover the elements of maqasid al-syariah as well as gauge the extent to which the Federal Constitution is able to support the implementation of the universal principles of the maqasid al-syariah. Using a comparative and harmonization approach, this study found that the Federal Constitution abounds with maqasid al-syariah pinciples, such as the protection of religion, life, intellect, lineage and property.Keywords: maqasid al-syariah federal Constitution, Islamic legal system